حالات امتلاء بحيرة بلطة الرملة خلال الفترات 1986 - 2018 ومواسم2022/2023 باستخدام التقنيات الحديثة - محمود الصديق التواتي (The Libyan Journal of Science, 2024)
A case study ,Al Ramla Baltat lake, this site is located within the southern boundary Al Jabal al-Akhdar region, about 14km south of the Al-Mukhaili vecinity where a temporary important natural lakes , in its catchment area created by torrents and floods. formed in a typical land composed of alluvial sediments, and it is a natural outlet for stream waters flow on the southern slope of Jabal al-Akhdar. The study aimed to The volume of water accumulation in the Balta Rainwater Lake during the 2022-2023 season, from the day it was filled on 11/27/2022 until its depletion in the dry season on 07/03/2023. The stages of the lakes’ emergence were also traced during the period 1986-2023, according to tracking images. satellite for the American Landsat 8 and the Sentinel A2l2 combat satellite. The author used layers and the analytical compositional approach based on visual data of the two satellites, aided by topographical and geological maps. The study was written. Image and map data were contributed to the ArcGIS era after and corrected using the eos.landviewer website, and using the NDSI tool. Measuring areas for pictures of the stages of the lake’s water lake thanks to loosed . The designers were surprised at the length of the follow-up period, and a small-scale attempt was made to mathematically flow the Ramla Valley. Based on the above, I set out to listen and patterns to reach the function in stages on the shores of the lake until its scars. It supported the temporal study during the period the study. The study found that the volume of water collected in the Ramla lake during 2022/2023 season was about 9.8 million cubic metres, and that its water dried up 100 days after it was filled, and that the daily loss of the lake was 98 thousand cubic meters per day. The volume of water collected during the period 1986 - 2023 amounted to 367.3 million cubic metres. The study recommends investing in the lake’s water by developing trenching technology in the Ramla area by creating an artificial lake of more than 8 meters deep to accommodate larger quantities of water.